Paradigm Shifts in Gender Narratives of Tafsīr al-Ibrīz through Oral Exegesis on Youtube - Muhammad Irsad; Abdul Mustaqim; Saifuddin Zuhri Qudsy (UIN Sunan Kalijaga Yogyakarta, 2024)
This article examines the book Tafsīr al-Ibrīz, written by KH Bisri Mustofa, a prominent Javanese exegesis. The book has been re-read and interpreted orally by his son, Gus Mus (KH Ahmad Mustofa Bisri), on his YouTube channel. This study highlights a new tradition in the digital era where Qur'anic exegesis is transmitted and transformed through both written texts and oral interpretations. This research employs a qualitative approach, using primary data from the official YouTube Channel of Gus Mus and secondary data from relevant scholarly literature. Document analysis and descriptive-analytic methods reveal a significant paradigm shift between the written and oral exegesis. Specifically, gender issues such as polygamy and women's leadership, which are presented with a gender-biased perspective in the written Tafsīr al-Ibrīz, are reinterpreted by Gus Mus with a focus on gender equality. This transformation is influenced by the socio-cultural context, Gus Mus's educational background, and the changing audience of the oral exegesis. The study incorporates gender equality theory, highlighting forms of gender inequality like marginalization, subordination, stereotyping, violence, and double burden. The findings suggest that Gus Mus's oral exegesis reflects an egalitarian interpretation, contrasting with the traditional views in Tafsīr al-Ibrīz, thus promoting fair treatment for both women and men. This research contributes to the discourse on gender and Qur'anic exegesis by demonstrating the dynamic nature of oral interpretation in the Indonesian pesantren context and its impact on advancing gender equality in Islamic thought.